Social inequalities in the risk of student burnout - Mareike Rußmann; Nicolai Netz; Karsten Becker; Marie-Christin Lenz (Journal of Public Health, 2026)
Abstract Aim Students in higher education face a high risk of burnout. To elucidate potential drivers and mitigators of the risk of student burnout, we extend the study demands-resources model by integrating (personal, financial, and social) private resources and key ascriptive characteristics (social background and gender) as potential markers of social inequality. Subject and methods We use data from “The Student Survey in Germany”. This unique dataset provides nationally representative information on students enrolled in German higher education institutions in the year 2021. On the basis of a large analytic sample ( n = 158,375) and using structural equation models (SEM), we can assess the plausibility of our theoretical assumptions altogether. Results We find that study resources and private resources (especially personal resources such as high self-efficacy) are substantially negatively correlated with the student burnout risk. While the burnout risk differs only slightly by social background, it is notably higher among women than among men, primarily because women consider their study demands to be higher and their personal resources to be lower. Conclusion Overall, our study illustrates that social groups differ in terms of perceived study demands and resources—and therefore require tailored support to reduce the risk of burnout.